algebra

posted by .

using quadratic formula 3y2=6+7y

3 y^2 -7y - 6 = 0
When using the quadratic formaul to find y, a = 3, b = -7 and c = -6

y = [-b +/- sqrt (b^2 -4ac)]/2a
= {7 +/- sqrt (49 + 72)}/6
= {7 +/- 11)/6
= +3 or -2/3

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math,algebra

    can someone help me out factor out this 0=16t^2-122t+180 i have so far this but the last one i am not sure 8(2t^2-14t + ?
  2. QUADRATIC EQUATION

    r^2+8r=48 First bring the 48 to the other side of the equation r^2+8r-48=0 Now you can use the quadratic formula. x=-b+-sqrt(b^2-(4ac)) ¯¯¯¯¯¯¯2a¯¯¯¯¯¯¯¯¯ So... a=1 b=8 c=-48 Now just plug the numbers into the quadratic …
  3. Math

    Use the quadratic formula to solve each of the following quadratic equations... 1. 2x^2-5x=3 2. 3x^2-2x+1=0 Rearrange the equation in quadratic formula form. 2x^2 -5x -3 = 0 Then use the formula. Tell me what you don't understand about …
  4. Math

    Find the exact solution to 6x^2+1=-8x by using the Quadratic Formula. A)-4+-(sqrt10) B)-4+-(sqrt22)/6 C)-2+-2(sqrt10)/3 D)-4+-(sqrt10)/6 I chose C x=-b+-(sqrtb^2-4ac)/2a x=--8+-(sqrt-8^2-4(6)(1))/2(6) x=8+-(sqrt64-24)/12 x=8+-(sqrt40)/12 …
  5. Algebra II

    Find the exact solutions to 6x^2+x+4=0 by using the quadratic formula. x=-b+-sqrtb^2-4ac/2a -1+-sqrt1^2-4(6)(4)/2(6) -1+-sqrt-95/12 -1-95/12 -96/12 x= -8 -1+95/12 94/12= 7.8333.. [-8, 7.83](answer)
  6. Algebra

    Quadratic Formula Using +/- for plus or minus Using \/ radical sign *****************_________ Formula: -b +/- \/b^2-4ac ********____________________ *****************2a Equation: x^2 - 25 = 0 Books says answer is 5 and -5. I can get …
  7. math

    15t^2+7t=2 The quadratic formula tells you that the solutions are: t = [-b +/-sqrt (b^2 - 4ac]/ (2a) In this case, a = 15, b = 7 and c = -2 solve the equation for t. What values for t will you get when you substitute the values you …
  8. Algebra

    1. Parent Quadratic Equation 2. Coordinate of the vertex 3. quadratic formula A. -b/2a B. y = 2x C.b^2 - 4ac D. y = a(x - h)^2 + k E. x = -b +/- (square root of) b^2 -4ac/2a I think the answers are: 1. B 2. C 3. E Are these correct?
  9. math help how do i do this

    Decide which part of the quadratic formula tells you whether the quadratic equation can be solved by factoring. −b b^2 − 4ac 2a Use the part of the quadratic formula that you chose above and find its value, given the following …
  10. math help plsss plsss

    Decide which part of the quadratic formula tells you whether the quadratic equation can be solved by factoring. −b b^2 − 4ac 2a Use the part of the quadratic formula that you chose above and find its value, given the following …

More Similar Questions